In situ experimentations for the compatibility and durability of the restorations: the case study of the Sassi of Matera - Ippolita Mecca (Vitruvio: International Journal of Architectural Technology and Sustainability)
The research intends to make a study of the interventions of restoration realized in a sample area, (“Sassi of Matera”), so as to establish an operating methodology with interpretative and implementable rules for the assessment of the concept of durability and service life in recovery interventions, starting from the preliminary phases of intervention, therefore that is from the project It is intended, in particular, to assess durability of the recovery intervention, analysing the aspects of subject compatibility, performance harmony and programmed maintenance. Starting from an initial check based on validation of the choices made by means of on site experiments and laboratory tests that conform to the regulations in force, and from predictions of the useful life of the utilised components, technological and subject compatibility and maintainability of these components, the objective is to formulate implementable technical intervention sheets which are an indispensable means for intervention planning and programming. Need underline that the durability of interventions must necessarily undergo the control and mastery of the traditional building techniques and a “programmed” design that is coherent with such interventions, guaranteeing a linguistic continuity of the landscape of the Sassi between its past and future, humbly respecting an environmental heritage of great value.